PENGARUH ELEVASI TERHADAP KEANEKARAGAMAN POHON DI KAWASAN GUNUNG TANGKOKO - Johanes Daniel Mewengkang; Johny S. Tasirin; Maria Y.M.A. Sumakud (COCOS, 2022)
Abstract Mount Tangkoko is an ideal place for this research because the Mount area stretches from the coastal elevation to an altitude of 1099 meters asl. This study aims to determine the effect of elevation on the diversity of tree species in the Tangkoko Mountain area. The results of this study identified 26 tree species and 20 families of 15 plots divided into three specified heights, namely 0 m above sea level (coastal forest), 300 m above sea level, and 600 masl. The diversity index shows a value of 2.43 at an elevation of 0 m, a value of 2.11 at an elevation of 300 m, and 1.95 at an elevation of 600 m, with the number of tree species at each elevation obtained sequentially amounting to 16, 13, and 11 tree species. Each height is dominated by The different tree species were Kleinhovia hospita tree with INP 55.22%, Cananga odorata tree at 300 m elevation with INP 94.92% and Spathodea campanulata tree at 600 m elevation with INP 101.52%. The tree attributes analyzed in the Tangkoko Mountain area show a general pattern which is indicated by the effect of elevation on the tree. However, statistical analysis shows a comparison of less visible differences in tree attributes (Diversity Index, Base area, Number of species per elevation, Number of families per elevation and tree density) and total tree diameter of the three elevations plotted. Key Word : tree diversity, tangkoko, elevation effect, altitude, ivi, important value index, lowland forest Pendahuluan Pada umumnya pohon mempunyai fungsi yang sangat besar bagi kehidupan dibumi, tidak hanya memproduksi oksigen sebagai senyawa esensial bagi makhluk hidup, pohon juga mempunyai fungsi edaphis yaitu merupakan tempat tinggal dari berbagai jenis makhluk hidup, berfungsi sebagai biomassa dan fungsi ekologis lainnya. Berbeda jenis pohon dapat juga mempunyai fungsi yang berbeda, seperti pada pohon bergenus ficus, pohon dengan genus ficus pada umumnya memiliki rongga pada batangnya yang digunakan primata tarsius untuk dijadikan sebagai sarang sekaligus tempat hewan ini melindungi diri dari predator. Tidak hanya untuk hewan, simbiosis ini juga dapat terjadi antar pohon dan tumbuhan. Pohon jelas menjadi salah satu objek untuk adanya simbiosis pada ekosistem huta